2017
DOI: 10.4103/jips.jips_97_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant extract denture cleansing on heat-cured acrylic denture base resin: An in vitro study

Abstract: Aim:Various chemical solutions have been recommended for denture disinfection; however, the immersion effect on the properties of denture base resin may also have effect on strength of the resin material. The purpose of this in vitro study was to compare and evaluate the flexural strength of heat-cure acrylic denture base resin by combination method of denture cleansing and plant extract immersion.Materials and Methods:In this study, ninety specimens of heat-cure acrylic denture base resin material were fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The results observed for flexural strength in fittydent denture cleanser group were in accordance with studies by Sharma et al [ 17 ] and Anjum et al [ 19 ] These studies observed no reduction in flexural strength when compared to the control group which is similar to our current observations. However, the reduction in flexural strength seen in thyme essential oil denture cleanser group is contradicting to the observations by Anjum et al , who had found increase in the flexural strength after immersion for 30 days.…”
Section: Discussionsupporting
confidence: 93%
“…The results observed for flexural strength in fittydent denture cleanser group were in accordance with studies by Sharma et al [ 17 ] and Anjum et al [ 19 ] These studies observed no reduction in flexural strength when compared to the control group which is similar to our current observations. However, the reduction in flexural strength seen in thyme essential oil denture cleanser group is contradicting to the observations by Anjum et al , who had found increase in the flexural strength after immersion for 30 days.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that the use of plant extract (Thyme) as denture cleanser on heat cure acrylic resin has increased structural strength as compared to denture-based resin. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Soaking in disinfectant solutions with chemical reagents manifests to be an effective procedure to reduce the number of contaminating organisms, but some chemical agents used for denture cleaning are known to damage acrylic resin and metal alloy materials [8]. An ideal denture cleanser should be "biocompatible, bactericidal, fungicidal, harmless, and nontoxic to the structure of denture; should effectively remove deposits, and should be easy to use" [9]. Synthetic chemical substances are substituted by natural products due to the growing curiosity in medicinal plants as a source of antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic chemical substances are substituted by natural products due to the growing curiosity in medicinal plants as a source of antimicrobial agents. Natural products, such as essential oils, are propitious curative tools for oral infection [9][10][11]. Plant essential oils are known to produce analgesic, anti-inflammatory, and antimicrobial effects [12].…”
Section: Introductionmentioning
confidence: 99%